Sibol - Dela Cruz, Rosebell Mikaella Jeanne Bautista 1991 (2014)
"Sibol tells the story of a young boy, Tonio and his family who are about to leave their home in the mountains. His parents agreed to sell their land to a company who plans to "develop" the area. While waiting for the full payment of their land, his father, Berto, tries to make ends meet by accepting various jobs and harvesting whatever he can find in their area and bringing it down to the market to sell. One day, Berto agress to take Tonio down with him to the market for the first time. The film explores the struggle of finding one's space to grow. Guided by Third Cinema and Social Realism, it tackles the commercialism thru Tonio's perspective. The filmmaker believes that because of advertising anchored on commercialism, we now have a distorted notion of what is ideal. And in a comercialist society, all of us are vulnerable to be unwitting victims to poverty."